Characteristic Of The Infanticide Concept: The Comparative Aspect - Kovtun, Oleksandr (Archives of Criminology and Forensic Sciences, 2022)
The article analyzes scientific papers dedicated to the issues of the murder of a newborn child by his/her mother. Both researchers and practitioners stressed the issue of murders of a newborn child by his/her mother, among them are: Antonian Yu.M., Baulin Yu.V., Borovitinov M.M. Borysov V.I., Hernet M.M. Liubavskyi A.D., Naumov A.V., Nekliudov N.A., Ostapenko L.A., Sainchyn O.S., Semeniuk I.S., Sosnina O.V., Stratonov V.M., Pashchenko O.Iu., Tsybulenko T.D., as well as foreign researchers: Richard von Krafft-Ebing, Iohan Zakharii Platner and others. As shown by the analysis, during different historical time periods, science constantly changed its opinion and attitude regarding such a social evil as the murder of a newborn child by his/her mother. On the other hand, there are still many unsolved issues, one of which we deem is uncertainty concerning the concepts and definitions of this particular type of crime. In research papers of multiple scientists, we come across the equation of the infanticide concept with child murder. For a precise definition of the infanticide concept, we analyzed the legislation of the Anglo-Saxon, Romano-Germanic legal system and other countries with a developed legal system, and also countries of the post-Soviet period, where liability for murdering juveniles, minors and newborn children was stipulated. A comparative characteristic of Ukrainian legislation during 1919–2022 has been provided. Provisions of criminal liability for the murder of a newborn child by his/her mother have been studied and difference from other qualified types of murders has been established. A personal viewpoint concerning the concept of deprivation of a person’s life has been expressed. It has been proven that the infanticide concept is not a universal concept for a number of reasons: each country uses its own version regarding this criminal activity; in Ukrainian legislation, as a result of various offenses, it is noted that the death of a young child, the fetus of a pregnant woman as well as a newborn child may take place (Part 1, paragraph 2, Article 115 Murder of the Criminal Code of Ukraine); Article 117 Infanticide; Article 134 Illegal abortion, i.e. artificial termination of pregnancy through external intervention in the woman’s body, which consequences due to criminal actions are the death of the child and others. Therefore, the generalized term infanticide, in certain cases, is not always appropriate to use, although this concept is quite broad. Thus, in order to understand and comprehend this concept, both theory and practice have been extensively analyzed, since there is no unified point of view as to understanding of when does this life begin that may be taken as a result of crime. After all, from the viewpoint of criminal law and signs of the composition of newborn child murder, the issue of primary and practical importance is not about the content of the human life concept, but about the issue of its beginning. For this reason, we provide several definitions for the concepts of infanticide, murder of a newborn child and murder of a human. We have come to a generalized conclusion that the beginning of a person’s life is laid not from the moment of their physical birth but much earlier. Thus we have analyzed the draft of the new criminal code (the part of murder, including of a newborn child). As a result, the introduced comparative-legal characteristic of concepts definition helps to actualize issues which, according to the author, can become the foundation for subsequent research and advancement of legislation, and thus enhance the activity of judicial, investigative and other agencies: that overall will lead to improvement in human rights protection.